Gahart's 2018 intravenous medications - Gahart, Betty L. (Elsevier, 2018)
Learn to administer more than 400 intravenous drugs safely and effectively with the #1 IV drug handbook! Now in its 34th edition, Gahart’s 2018 Intravenous Medications: A Handbook for Nurses and Health Professionals continues to be a trusted resource for its accuracy, quick-reference format, and comprehensive coverage of IV drugs. The latest edition includes approximately 15 important new drug monographs, along with updates to existing monographs. Each drug listing includes its generic name, trade name(s), drug category, pH, dosages and dose adjustments, dilution, incompatibilities, rate of administration, actions, indications and uses, contraindications, precautions, drug/lab interactions, side effects, and antidote. This user-friendly book contains all of the clinically relevant information you’ll need for the safe administration of IV drugs